Insect Communities in the Three Different Forest Habitats of Sungai Lalang Forest Reserve with Emphasis on Selected Orders of Insects - Haneda, Noor Farikhah (2004)
A study to investigate the abundance and diversity of insects in forest habitat of different age after logging was conducted in the Sungai Lalang Forest Reserve, Selangor, Malaysia. The main objectives of the study were to determine (i) the dominant insect in different forest habitats, (ii) the biodiversity of insects, and (iii) the assemblage of insects that can be used as bioindicator. Three different forest habitats were selected, namely: Primary forest, Five-year-old logged forest and Ten-year-old logged forest.